Could Artificial Intelligence be the Subject of Criminal Law? - Mahardhika, Vita; Astuti, Pudji; Mustaffa, Aminuddin (Faculty of Law, Universitas Sebelas Maret, 2023)
The use of artificial intelligence can increase productivity and efficiency in various sectors of life. However, it can also potentially cause legal problems especially criminal law if they result in losses. The subject of law in determining who should be responsible is a separate issue. This research examines whether technology using artificial intelligence can be used as the subject of criminal law so that criminal responsibility can be held. This research is normative juridical research with a statutory, conceptual approach and cases related to artificial intelligence and criminal law issues. The study shows that the ability to analyze and make decisions possesed by artificial intelligence can be indicated as